PP2C-Mediated ABA Signaling Pathway Underlies Exogenous Abscisic Acid-Induced Enhancement of Saline–Alkaline Tolerance in Potato (Solanum tuberosum L.) - Xinhui Yang; Zisheng Liu; Jun Chen; Wangjun Zhang; Wenhui Yang; Congang Shen; Yichen Kang; Shuhao Qin (Plants)
Saline–alkali stress severely inhibited potato growth, yield, and quality, and exogenous abscisic acid (ABA) played an important role in plant stress resistance. In this study, potato tissue culture seedlings were used as experimental materials, the control group was cultured in the MS medium without adding any substances, and the treatment group was cultured in MS medium supplemented with 50 mmol/L NaHCO3 or 50 mmol/L NaHCO3 + 38 µM ABA, respectively. To explore the effect of exogenous ABA on the biological characteristics of potato plants under saline–alkali stress, a genetic improvement strategy was designed based on PP2C (PGSC0003DMT400046381), a key gene of the ABA signaling pathway. The results showed that saline–alkali stress led to leaf greening, wilting, and root development stunting, while exogenous ABA treatment significantly alleviated stress damage. PP2C negatively regulates ABA signaling. SnRK2s are activated when PP2Cs are inactivated during the ABA response. Compared with wild-type CK, it was found that TG lines had increased SOD and POD activities, increased carotenoid and ABA contents, reduced the increase in Na+ content and the decrease in K+ content, and interfered with PP2C (PGSC0003DMT400046381) to significantly enhance potato salinity–alkali resistance. This study provides a theoretical basis and technical path for the analysis of ABA-mediated plant stress resistance mechanism and the breeding of potato stress resistance varieties.